Verification of type 1 diabetes mellitus model - Sri Vathsavai Neelima (2014)
This study focuses on verifying Blood Glucose (BG) levels simulated using real patients input of meal and insulin details. This is important as diabetes pattern has been going up in the population over the last 10 years. It would be useful to have a personalized model for each diabetic patient to be able to predict supposed BG rise and falls so that diabetic patient can better manage their condition without constant supervision. This is the aim for the collaboration between KK Women’s and Children’s Hospital’s Endocrinology Centre and NTU’s School of Computer Engineering.